2013
DOI: 10.1024/0300-9831/a000178
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity Induced by Dietary Oxidized Sunflower Oil in Rats: Pro- and Antioxidant Effects of α-Tocopherol

Abstract: This study highlighted the pro-oxidative functions of α-tocopherol (αT) on the heart antioxidant system and tissue histopathology of oxidized sunflower oil (OSO)-exposed rats.Four groups of male Wistar rats were fed with different diets: 1) control diet containing FSO (fresh sunflower oil); 2) diet containing 5 % OSO; 3) diet containing 5 % OSO, supplemented with 600 mg αT kg-1; and 4) diet containing 5 % OSO, supplemented with 1200 mg αT kg-1. The hearts were then isolated, and the antioxidant enzymatic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to [206] , vitamin E, vitamin C and lipoic acid protect the arachidonic acid level in the brains of diabetic and non-diabetic rats. However, when a combination of high doses of vitamin E with oxidized sunflower oil is used, this vitamin presents pro-oxidant action [207] .…”
Section: Resultsmentioning
confidence: 99%
“…According to [206] , vitamin E, vitamin C and lipoic acid protect the arachidonic acid level in the brains of diabetic and non-diabetic rats. However, when a combination of high doses of vitamin E with oxidized sunflower oil is used, this vitamin presents pro-oxidant action [207] .…”
Section: Resultsmentioning
confidence: 99%
“…During the heating process, reactive oxygen species, such as hydroperoxides, are produced (26) and cause oxidative stress-induced cytotoxicity (27,28). The MDA is one of the end products of lipid peroxidation that is considered as an index for cell damage (29).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, consumption of oxidized rapeseed oil for 112 days induced transient myocardial lipidosis characterized by accumulation of fat droplets in myocardial fibers of rats (Charlton et al, 1975). Rouaki et al (2013) reported that dietary oxidized sunflower oil induced extensive necrosis of heart tissue, increased body weight and LPO levels, and decreased catalase (CAT) and glutathione peroxidases (GPx) activities in rats. Again, other studies found that dietary heated palm oil diet for 16 weeks significantly increased the myofiber width and area, and induced necrosis in cardiac tissue of rats (Kamisah et al, 2016;Leong et al, 2008).…”
Section: Cardiotoxicitymentioning
confidence: 99%